Distinct patterns of brain activity mediate perceptual and motor and autonomic responses to noxious stimuli - Laura Tiemann (Nature Portfolio, 2018)
Pain is a complex phenomenon involving not just the perception of pain, but also autonomic and motor responses. Here, the authors show that these different dimensions of pain are associated with distinct patterns of neural responses to noxious stimuli as measured using EEG.